Possibilities of tourism development in Opovo Municipality - Aleksander Stojanov; Dragan Ugrinov; Vuk Radojević (Ekonomika Poljoprivrede (1979), 2010)
On the territory of Opovo municipality there are many kinds of natural (hydrologic, climatologic and bio-geographical) and anthropogenic touristic values (churches, galleries, monuments of culture). Most of the touristic values, both natural and antropogenic ones arent attractive enough for the tourists. Therefore we can speak only about the potentials for rural tourism development Development of rural tourism gave good economic results in the countries of Western Europe. Surely, there is a great number of less developed countries or those in development that have lost the race of economic development to highly developed countries-and those countries see their chance in rural tourism development. Their main potentials are based on ecologically preserved rural area, anthropogenic heritage, natural resources and healthy food. Although country tourism has been practiced since the year 2000, the results are far behind the actual possibilities. However, there are expectations that nowadays trend, which is in stagnation, will in the next period become a rising trend, considering the fact that tourist agency "Turist" is taking steps and specifc actions to promote rural tourism development The term rural tourism, as well as the factors influencing competitiveness of a touristic destination, is defned in this paper with an accent on ecology, environmental protection and sustainable development.